Childhood negative dental experiences and tooth loss in later life: A 25-year longitudinal study in Sweden. (October 2019) - Bernabé, Eduardo; Lie, Stein A.; Mastrovito, Berit; Sannevik, Josefin; Astrom, Anne N.
Abstract: Objective: To explore the association between childhood NDEs and changes in tooth loss over 25 years among Swedish older adults, and the role of dental visits in explaining such an association. Methods: We used data from 6154 adults, members of a cohort study that started in 1992 when participants were 50 years old. All data were self-reported through postal questionnaires (6 in total, one every 5 years). Information on childhood NDEs was collected at baseline only. Tooth loss was the repeated outcome measure. Mixed effects logistic regression models were used to test the association between childhood NDEs and tooth loss adjusting for confounders. Results: Childhood NDEs was positively associated with greater odds of experiencing tooth loss and its rate of change over the 25-year period. Although having a dental visit within the past year was positively associated with childhood NDEs and inversely associated with incidence of tooth loss, it explained very little of the association between childhood NDEs and tooth loss in later life. Conclusion: The findings underscore the long-lasting damaging effects of early life NDEs on adult oral health. Clinical significance: A positive patient-dentist relationship starts early in life. Early visits to the dentist are essential to build an enduring relationship of trust between people and healthcare providers.